Advances in the detection of water content of plant-based food materials - WANG Lejun; XING Youcheng; NIU Yanli; CHEN Kai; JIANG Fatang (Shipin yu jixie)
This reviewed summarized the research status of water content detection methods of plant-based food materials, analyzed the water content detection devices, advantages, disadvantages and applications, and discussed the application of water content detection in different types of plant-based food materials. The advantages of hot air drying, microwave method, Karl Fischer method, absolute dry nitrogen purge method, spectral technology and imaging technology were highlighted, and the future development direction of water content detection of plant-based food materials was prospected.